Desenvolvimento de processos tecnológicos para preservação e descontaminação de alimentos - Perez, Shirly Marleny Lara (Universidade Federal de São Carlos, 2020)
Contamination of foods caused by microorganisms occurs through their handling and or processing, which can change their physical-chemical characteristics and decrease shelf life, and cause infection. The objective of this work was to evaluate the effect of gaseous ozone (O3) and to the combination of ultraviolet light and aqueous ozone, to analyze the best protocol that makes it available to inactivate bacteria contained superficially on beef with in natura contaminations and by Escherichia coli. A prototype for gaseous ozone was designed, and the evaluation in inert samples submitted to gaseous ozone decreased around 3,88 Log (CFU / cm2) of E. Coli in 30 minutes, and for beef samples with in natura contamination, the microbial reduction was 50% after 10 minutes. Experiments were conducted to evaluate the microbiological behavior of the meat simulating exposure situations in the 12-hour butcher shop, the results showed that in the 30 minutes exposure time there was a reduction of 2,18 Log (CFU / cm2), and in the second refrigeration the load was inactivated, however, the control sample under equal temperature conditions and without treatment had a proliferation of 1,7 Log (CFU / cm2). To evaluate the combined treatments of ozone in aqueous phase and ultraviolet light, the equipment was built and tested against E. coli on contaminated beef. Samples were added to 10 repetitive cycles for the combined and isolated treatments. For the isolated treatment of ultraviolet light, a reduction of 1.3 Log (CFU / cm²) was obtained at the end of cycles and for the ozone treatment, there was no significant difference in microbial inactivation (p <0,05), but there was a difference for the final control sample of the experiment, which grew by 0,6 Log (CFU / cm²), the combined cycles showed similar inactivation of 0,7 Log (CFU / cm²) approximately and all combined and isolated treatments showed food preservation avoiding the exponential proliferation of microorganisms. The organoleptic properties of the meat were evaluated after the treatments, the pH was checked, the protein quantified by the Bradford method, and TBARS tests were performed for both prototypes and gaseous ozone, histological slides were also analyzed for structural damage and water holding capacity. Organoleptic evaluations did not show significant differences about the control samples, for both technologies; gaseous ozone and combination of ultraviolet light and aqueous ozone and showing potential for decontamination of food without deteriorating its quality.
Development of technological processes for food preservation and decontamination
Keywords: Carne; Ozônio; Luz ultravioleta; Descontaminação; Bactérias; E. coli; UV; O3; Meat; Ozone; UV light; Decontamination; Bacteria; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS